The situation of refugees and escapees from Raciborski, Głubczycki and Kłodzki counties over the Czechoslovakian side of the boarder = Sytuacja uchodźców i uciekinierów z powiatów raciborskiego, głubczyckiego i kłodzkiego po czechosłowackiej stronie granicy w latach 1945-1951 - Pałys, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1945 Czechoslovakia made claims for the southern parts of Upper Silesia and Kłodzko Valley - the lands partially inhabited by people of Moravian and Czech descent. e attempts to introduce Czechoslovakian influences conjured the reaction of the Poles. As the effect, groups of escapees started to emerge in Náchod, Opava and Karniów regions. Their presence was at first used as a legitimization for Prague`s territorial claims.
Keywords: Czechs from Kłodzko; Moravians; Polish-Czechoslovakian borderland; argument about borders; refugees; kłodzcy Czesi; Morawianie; granica polsko-czechosłowacka; uchodźcy